Association of MAPK4 and SOX1-OT gene polymorphisms with cleftlip palate in multiplex families: A genetic study - Praveen Kumar Neela; Srinivas Reddy Gosla; Akhter Husain; Vasavi Mohan; Sravya Thumoju; Rajeshwari BV (Tabriz University of Medical Sciences, 2020)
Background. Cleft lip and palate (CLP) is a common congenital anomaly. Many genes, like MAPK4 andSOX-1OT, are associated with its etiology in different populations. High-risk markers on these genesreported in other populations were not studied in our population. Hence, the study aimed to determinethe association of MAPK4 and SOX-1OT polymorphisms in CLP in multiplex families. Methods. Based on inclusion and exclusion criteria, we selected 20 multiplex CLP families for thiscase‒control study, in which the affected individuals and healthy controls selected from these familieswere compared. Fifty subjects affected with cleft and 38 unaffected subjects were included in the study.The polymorphisms studied for the association consisted of rs726455 and rs2969972 in the genes SOX-1OT and MAPK4, respectively. DNA was isolated and sent for genotyping using the MassArray method.Plink, a whole-genome association analysis toolset, was used for statistical analysis. Results. Both polymorphisms followed Hardy-Weinberg equilibrium. The rs726455 of SOX-1OTyielded a P-value of 0.983 and an allelic odds ratio (OR) of 0.983. For rs2969972 of MAPK4, the P-valuewas 0.04 (significant), and the allelic OR was 0.51. Minor allele frequency (MAF) in the unaffectedsubjects was more than the MAF in the affected subjects for rs2969972. Conclusion. The results suggested that polymorphism rs726455 on SOX-1OT was not associated withfamilial cases of CLP. Since MAF in the unaffected subjects was more than the MAF-affected subjects,rs2969972 on MAPK4 is protective in the multiplex families.